2018
DOI: 10.1021/acs.jpcc.7b09562
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Upconversion Luminescence in a Highly Transparent Triply-Doped Gd3+–Tm3+–Yb3+ Fluoride–Phosphate Glasses

Abstract: We report near-infrared to ultraviolet (UV) upconversion emissions in triply-doped Gd3+–Tm3+–Yb3+ fluoride–phosphate glasses. Emission at 310 nm, originated from the Gd3+:6P7/2 → 8S7/2 transition, was observed for the first time in glasses. The high-purity glasses prepared exhibit extended transparency in the UV down to 200–250 nm. The mixed fluoride–phosphate environment of the rare-earth ions was characterized by means of NMR techniques using scandium as a diamagnetic mimic for the luminescent species, for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 57 publications
4
24
1
2
Order By: Relevance
“…All experimental data can be perfectly fitted using linear function with the slopes of 1.79–2.22 on a log-log plot giving n ≈ 2. We concluded that the observed 2 H 11/2 – 4 I 15/2 , 4 S 3/2 – 4 I 15/2 and 4 S 3/2 – 4 I 15/2 transitions in NaYF 4 : Yb, Er, and Gd samples originated from two-photon process [ 37 ] irrespective of Gd 3+ co-doping concentration. Figure 4 d–f present integral emission intensity of the blue and red emission lines as a function of the pump laser power for NaYF 4 : Yb, Tm, and Gd powders.…”
Section: Resultsmentioning
confidence: 99%
“…All experimental data can be perfectly fitted using linear function with the slopes of 1.79–2.22 on a log-log plot giving n ≈ 2. We concluded that the observed 2 H 11/2 – 4 I 15/2 , 4 S 3/2 – 4 I 15/2 and 4 S 3/2 – 4 I 15/2 transitions in NaYF 4 : Yb, Er, and Gd samples originated from two-photon process [ 37 ] irrespective of Gd 3+ co-doping concentration. Figure 4 d–f present integral emission intensity of the blue and red emission lines as a function of the pump laser power for NaYF 4 : Yb, Tm, and Gd powders.…”
Section: Resultsmentioning
confidence: 99%
“…As for compound 1, when it was excited by the wavelength of 290 nm, its photoluminescence emission spectrum exhibits one sharp emission band in the narrow range of 306-328 nm with the peak locating at 313 nm (Figure 3). This emission can be assigned to the characteristic emission of the 4f electron intrashell transition of 6 P 7/2 → 8 S 7/2 (Gd 3+ ) [26,27]. The CIE system characterizes colors by two color coordinates x and y which specify the point on the chromaticity diagram.…”
Section: Solid-state Photoluminescencementioning
confidence: 99%
“…Among them, the phosphate network is considered an efficient optical host due to its high thermal stability, high transparency over the UVvisible wavelength range, and especially good solubility of rare-earth ions. The lack of chemical durability of the phosphate glass network is usually treated via inlaying the phosphate network with suitable alkali and alkaline earth oxides [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, heavy metals oxyfluorophosphate glasses are promising hosts for several photonic applications because they have both oxides and fluorides characteristics. At the low ratios of phosphate/fluoride, fluoride ligation dominates on the local environment of the Re 3+ ions, which is significant for high quantum yield and phonon-assisted energy transfer processes [13][14][15] . Trivalent erbium ion Er 3+ is usually used in various hosts as a dopant because of its peculiar optical properties.…”
Section: Introductionmentioning
confidence: 99%